The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jp301670f
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Calculation of Anharmonic Vibrational Frequencies Using Force Fields Derived from Density Functional Theory

Abstract: The calculation of anharmonic vibrational frequencies for a set of small molecules has been examined to explore the merit of applying such computationally expensive approaches for large molecules with density functional theory. The performance of different hybrid and gradient-corrected exchange-correlation functionals has been assessed for the calculation of anharmonic vibrational frequencies using second-order vibrational perturbation theory with two-and four-mode couplings and compared to the recently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…Currently, modern computational chemistry yields results comparable to the most accurate experimental measurements [61]. Furthermore, the interpretation of experimental vibrational spectra is much easier and accurate owing to calculated harmonic and anharmonic [62] vibration transitions [63]. …”
mentioning
confidence: 99%
“…Currently, modern computational chemistry yields results comparable to the most accurate experimental measurements [61]. Furthermore, the interpretation of experimental vibrational spectra is much easier and accurate owing to calculated harmonic and anharmonic [62] vibration transitions [63]. …”
mentioning
confidence: 99%
“…30%‐40% additional Hartree‐Fock exchange, while anharmonic studies using VPT2 have shown that the B97‐1 functional outperforms B3LYP and that the optimum hybridization is ca. 20%, in line with the prediction of other molecular properties . Another method for checking the accuracy of harmonic calculations is therefore to compare the quality of the harmonic calculations with harmonic experimental frequencies that are extrapolated from vibrational spectra of small molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that choice of basis set is of considerable importance when calculating accurate harmonic and anharmonic frequencies more generally . This can be such a significant source of computational cost and error, that basis sets tailored to specific vibrational coordinates are in development, and Pople basis sets are commonly used as a compromise between accuracy and computational cost, particularly during anharmonic calculations . At the same time, uncontracting the core basis functions in Pople‐type atom‐centered basis sets has been shown to improve calculations of core‐electron properties, such as core‐electron binding energies, and provides a systemic way of testing improvements in basis set quality when describing the core region of molecules as well as σ‐orbitals described by the additional s ‐functions, which are fewer in the Pople basis sets than other families of basis set …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmonic frequencies were scaled using a scaling factor of 0.9682. 2,50,65 In principle it would be possible to derive scaling factors for different excited state methods. However, there is currently a lack of experimental data encompassing a wide range of functional groups to make this reliable, and we assume here that scaling factors derived for the ground state can be applied with no additional modifications following previous excited state frequency benchmarking studies.…”
Section: Computational Detailsmentioning
confidence: 99%